IFITMs exhibit antiviral activity against Chikungunya and Zika virus infection via the alteration of TLRs and RLRs signaling pathways - Nuttamonpat Gumpangseth; Paola Mariela Saba Villarroel; Abibatou Diack; Thanaphon Songhong; Sakda Yainoy; Rodolphe Hamel; Wipaporn Khanom; Phanit Koomhin; Chuchard Punsawad; Anon Srikiatkhachorn; Dorothée Missé; Phoonthawee Saetear; et al. (Scientific Reports, 2025)
Chikungunya virus (CHIKV) poses a significant challenge as there are currently no targeted antiviral drugs or vaccines to combat this infection. Here, we demonstrate that interferon-induced transmembrane proteins (IFITMs), including IFITM1, IFITM2, and IFITM3, which are interferon-stimulated genes (ISGs), inhibit CHIKV infection in human skin fibroblasts. Overexpression of IFITMs in cells restricts viral infection, whereas knockdown of IFITMs enhances viral infection. IFITMs overexpression causes a substantial upregulation of antiviral genes, namely TLR3, TLR7, TLR8, and TLR9, and their downstream signaling molecules such as TRADD, IRAK1, TRAF6, and MAP3K7, involved in TLRs signaling pathways. Furthermore, the DHX58 gene encoding the LGP2 protein, a negative regulator of RIG-I in RLRs signaling pathways, was downregulated in the overexpressed cells. Transcription factors including interferon regulatory factors (IRF) 3/5/7, which are downstream signaling components of both TLR and RLR signaling pathways, were also upregulated, resulting in enhanced IFNs signaling. IFITMs not only inhibits the early and late stages of viral infection but can also alter the antiviral innate-immune response to restrict CHIKV infection in human skin fibroblasts. Additionally, IFITMs exhibit their antiviral activity against Zika virus (ZIKV). Altogether, these results show the broad-spectrum antiviral property of IFITMs against arboviruses in foreskin cells.
Keywords: Mosquito-borne diseases and control; Viral Infections and Vectors; Viral Infections and Outbreaks Research